Influence of Air Plasma Pretreatments on Mechanical Properties in Metal-Reinforced Laminated Wood - Dahle, Sebastian; Srinivasa, Kavyashree; Žigon, Jure; Cheumani Yona, Arnaud Maxime; Avramidis, Georg; Viöl, Wolfgang; Petrič, Marko (Frontiers in Materials, 2022)
Using wood-based materials in building and construction is constantly increasing as environmental aspects and sustainability gain importance. For structural applications, however, hybrid material systems are often needed to fulfil the specific mechanical requirements of individual applications. Particularly metal reinforcements are common solutions to enhance mechanical properties of wooden structural elements. Metal-reinforced wood components further help to reduce cross-sectional sizes of load-bearing structures, improve the attachment of masonry or other materials, enhance the seismic safety and tremor dissipation capacity, as well as the durability of the structural elements in highly humid environments and under high permanent mechanical load. A critical factor to achieve these benefits, however, is the mechanical joint between the different material classes, namely the wood and metal parts. Currently, this joint is formed using epoxy or polyurethane (PU) adhesives, the former yielding highest mechanical strengths, whereas the latter presents a compromise between mechanical and economical constraints. Regarding sustainability and economic viability, the utilization of different adhesive systems would be preferable, whereas mechanical stabilities yielded for metal-wood joints do not permit for the use of other common adhesive systems in such structural applications. This study extends previous research on the use of non-thermal air plasma pretreatments for the formation of wood-metal joints. The plasma treatments of Norway spruce (Picea abies (L.) Karst.) wood and anodized (E6/EV1) aluminum AlMgSi0.5 (6060) F22 were optimized, using water contact angle measurements to determine the effect and homogeneity of plasma treatments. The adhesive bond strengths of plasma-pretreated and untreated specimens were tested with commercial 2-component epoxy, PU, melamine-urea formaldehyde (MUF), polyvinyl acetate (PVAc), and construction adhesive glue systems. The influence of plasma treatments on the mechanical performance of the compounds was evaluated for one selected glue system via bending strength tests. The impact of the hybrid interface between metal and wood was isolated for the tests by using five-layer laminates from three wood lamellae enclosing two aluminum plates, thereby excluding the influence of congeneric wood-wood bonds. The effect of the plasma treatments is discussed based on the chemical and physical modifications of the substrates and the respective interaction mechanisms with the glue systems.